Comparison of diagnostic accuracy for nonocclusive mesenteric ischemia in models with biomarkers including intestinal fatty acid–binding protein in addition to clinical findings. Issue 2 (February 2019) - Matsumoto, Shokei; Shiraishi, Atsushi; Kojima, Mitsuaki; Funaoka, Hiroyuki; Funabiki, Tomohiro; Saida, Takafumi; Kitano, Mitsuhide
Abstract : BACKGROUND: Nonocclusive mesenteric ischemia (NOMI) is an acute and life-threatening gastrointestinal disorder, requiring rapid therapeutic intervention for ischemic bowel. However, its rapid detection remains challenging. This retrospective, observational study was aimed at comparing the diagnostic accuracy for NOMI in models of biomarkers, including intestinal fatty acid–binding protein (I-FABP), and clinical findings. METHODS: All consecutive patients who presented to the emergency department of the study hospital with suspected NOMI were prospectively enrolled. Receiver operating characteristic analysis compared the diagnostic accuracy of I-FABP with traditional biomarkers (white blood cell count, C-reactive protein, lactate, creatine kinase, and D-dimer) alone and in combination with the baseline model established from clinical findings. RESULTS: Of 96 patients with suspected NOMI, 25 (26.0%) were clinically diagnosed with NOMI. In-hospital mortality was higher in patients with NOMI than those with other conditions (56.0% vs. 4.2%, p < 0.001). Receiver operating characteristic analyses revealed that the I-FABP model had the highest area under the curve (0.805) in the diagnosis of NOMI, compared with other biomarkers. The diagnostic model of clinical findings including age, cardiovascular disease history, undergoing hemodialysis, hypotension, and consciousness disturbance in combination with I-FABP showed the best discrimination (area under the curve, 0.883), compared with other biomarkers. The bootstrap optimism estimate showed the lowest discrimination among the other models with other biomarkers (0.006). CONCLUSION: The usefulness of I-FABP for final diagnosis of NOMI in patients with clinically suspected NOMI at the emergency department was internally validated. Further external validation study is warranted. LEVEL OF EVIDENCE: Diagnostic test, level III. Abstract : Supplemental digital content is available in the text.